Vangl2, a Core Component of the WNT/PCP Pathway, Regulates Adult Hippocampal Neurogenesis and Age-Related Decline in Cognitive Flexibility - Koehl, Muriel; Ladevèze, Elodie; Montcouquiol, Mireille; Abrous, Djoher Nora (Frontiers in Aging Neuroscience, 2022)
Decline in episodic memory is one of the hallmarks of aging and represents one of the most important health problems facing western societies. A key structure in episodic memory is the hippocampal formation and the dentate gyrus in particular, as the continuous production of new dentate granule neurons in this brain region was found to play a crucial role in memory and in age-related decline in memory. As such, understanding the molecular processes that regulate the relationship between adult neurogenesis and aging of memory function holds great therapeutic potential. Recently, we found that Vang-gogh like 2 (Vangl2), a core component of the Planar Cell Polarity (PCP) signaling pathway, is enriched in the dentate gyrus of adult mice. In this context, we sought to evaluate the involvement of this member of the Wnt/PCP pathway in both adult neurogenesis and memory abilities in adult and middle-aged mice. Using a heterozygous mouse model carrying a dominant-negative mutation in Vangl2 gene, called Looptail (Vangl2Lp), we show that alteration in Vangl2 expression decreases the survival of adult-born granule cells and advances the onset of decrease in cognitive flexibility. Inability of mutant mice to erase old irrelevant information to the benefit of new relevant ones highlights a key role of Vangl2 in interference-based forgetting. Taken together, our findings show that Vangl2 activity may constitute an interesting target to prevent age-related decline in hippocampal plasticity and memory.